Dynamics Analysis of Modified Leslie-Gower Model with Simplified Holling Type IV Functional Response - Nur Suci Ramadhani; Toaha Toaha; Kasbawati Kasbawati (Department of Mathematics, Hasanuddin University, 2021)
In this paper, the modified Leslie-Gower predator-prey model with simplified Holling type IV functional response is discussed. It is assumed that the prey population is a dangerous population. The equilibrium point of the model and the stability of the coexistence equilibrium point are analyzed. The simulation results show that both prey and predator populations will not become extinct as time increases. When the prey population density increases, there is a decrease in the predatory population density because the dangerous prey population has a better ability to defend itself from predators when the number is large enough.